2019
DOI: 10.1007/s40279-019-01110-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Risk Factors Associated with Running-Related Injuries: A Systematic Review

Abstract: Background Running is a popular form of physical activity with many health benefits. However, the incidence and prevalence of running-related injuries (RRIs) is high. Biomechanical factors may be related to the development of RRIs. Objective This systematic review synthesizes biomechanical risk factors related to the development of RRIs in non-injured runners. Methods PubMed, Web of Science, CINAHL, Embase, and SPORTDiscus were searched in July 2018 for original peerreviewed prospective studies evaluating pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
159
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 114 publications
2
159
0
2
Order By: Relevance
“…Hundreds of millions of citizens participate in sports, among which running is widely known. Injury remains high with the popularity of running, with 19.4% to 79.3% sustaining a running-related injury annually [1]; patellofemoral pain syndrome (PFPS) is one of the most common running injuries, exhibiting the highest incidence of 17% in the specific pathologies of running-related injuries [2]. Increased patellofemoral joint stress (PFJS) was determined as an important pathogenic factor [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of millions of citizens participate in sports, among which running is widely known. Injury remains high with the popularity of running, with 19.4% to 79.3% sustaining a running-related injury annually [1]; patellofemoral pain syndrome (PFPS) is one of the most common running injuries, exhibiting the highest incidence of 17% in the specific pathologies of running-related injuries [2]. Increased patellofemoral joint stress (PFJS) was determined as an important pathogenic factor [3].…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed bias (Ceyssens, et al, 2019). The remaining 23 articles received a low risk of bias score.…”
Section: Methodsological Quality and Bias Assessmentmentioning
confidence: 99%
“…An assessment of risk bias was determined based on the work of Lopes, et al (2012) and adapted by Ceyssens, et al (2019). The criteria used by Lopes, et al (2012) was adapted for our work, with the scoring system based on the same 10 items: (1) definition of injury clearly described, (2) prospective design that presents incidence or prevalence data, (3) description of level of pitchers (e.g., recreational or professional level), (4) the process of inclusion of athletes in the study was random (i.e., not by convenience) or the data collection was performed with the entire target population; (5) data analysis performed with at least 80% of the athletes included in the study; (6) injury data reported by pitchers; (7) same mode of injury data collection used; (8) injury diagnosis conducted by a medical professional; (9) follow-up period of at least 6 months;…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Risk factors for running-related injury (RRI) have been explored in several original studies and synthesized in various systematic reviews (Ceyssens et al 2019;Saragiotto et al 2014;Hulme et al 2017). Although the attempts to identify risk factors for RRI in the original articles included in these systematic reviews have been extraordinary, 86 out of 89 studies used a relative measure of association (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Absolute differences have been reported in biomechanical studies, although these differences are normally between injury groups and not between exposure groups (Ceyssens et al 2019;Powers 2010). In prospective cohort studies, the most common analytical approach has been to compare differences in biomechanical measures, such as external knee adduction moments (Dudley et al 2017), ankle eversion range of motion and eversion velocity (Kuhman et al 2016), and hip strength (Finnoff et al 2011), between injured and non-injured runners.…”
Section: Introductionmentioning
confidence: 99%